Analysis of surgical site infections in orthopedic patients in a hospital in Paraná - Longo, Laura Bazzi (2021)
Surgical site infections are found in 14-16% of hospitalized patients, and those related to orthopedic surgeries are considered severe. Therefore, the determination of risk factors is necessary to identify situations that predispose to the development of this infection. Aiming to list the risk factors related to surgical site infections at a university hospital in Paraná, in a retrospective cross-sectional descriptive study, 125 medical records of individuals who had undergone orthopedic surgery and developed postoperative infection were analyzed. Thus, it was possible to find a profile of patients more susceptible to developing this complication, in which, 41.0% of the patients were identified as healthy preoperatively, 61.6% of the surgeries were clean, 63.2% used orthopedic implant in their treatment and surgical treatment of closed fractures prevailed. The overall incidence of infection was 2.0% and the most prevalent microorganisms in the sample were Staphylococcus aureus, Enterobacter cloacae and Escherichia coli with 7.2% each. Comparing with the literature covered, differences are found in the prevalence of risk factors, due to the differences of each population. The identification of these risk factors is of utmost importance for the prevention of surgical site infections. Finally, new studies should still be carried out to validate the risk factors found.